If g(x-1)= x^(2) + 2, then g(x)=? Answer = x^(2) + 2x + 3 Thanks for the help
Follow Math Help Forum on Facebook and Google+
Let's define f(x) = g(x - 1) = x^2 + 2. Then what is f(x + 1)?
Originally Posted by benny92000 If g(x-1)= x^(2) + 2, then g(x)=? Answer = x^(2) + 2x + 3 Thanks for the help , so if then .
Originally Posted by Prove It , so if then . Strictly speaking, one needs to consider g((x+1)-1): this is the result of substituting x+1 for x in the expression for g(x-1).
Yet another approach: given g(x- 1)= x^2+ 2, let y= x- 1 so that x= y+ 1. Then g(x- 1)= g(y)= (y+ 1)^2+ 2= y^2+ 2y+ 3. And, of course, it follows that g(x)= x^2+ 2x+ 3.
View Tag Cloud